CONVERSATIONAL STYLE IN RUSSIAN LANGUAGE - Utemuratova Zaruxan Ajimuratovna (Western European Studies, 2024)
Conversational style refers to the peculiarities of spoken language of native speakers of a literary language. Conversational style is characteristic of the oral form of a literary language, however, it can occur in the written form of a language in some genres, for example, in private letters, announcements, explanatory notes and others
Keywords: Conversational style; native speakers; literature